1999
DOI: 10.1523/jneurosci.19-02-00619.1999
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen/Glucose Deprivation in Hippocampal Slices: Altered Intraneuronal Elemental Composition Predicts Structural and Functional Damage

Abstract: Effects of oxygen/glucose deprivation (OGD) on subcellular elemental composition and water content were determined in nerve cell bodies from CA1 areas of rat hippocampal slices. Electron probe x-ray microanalysis was used to measure percentage water and concentrations of Na, P, K, Cl, Mg, and Ca in cytoplasm, nucleus, and mitochondria of cells exposed to normal and oxygen/glucose deficient medium. As an early (2 min) consequence of OGD, evoked synaptic potentials were lost, and K, Cl, P, and Mg concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 75 publications
5
72
2
1
Order By: Relevance
“…In the present study, direct measurements of total Ca in individual mitochondria show that mitochondria of NMDA-overstimulated hippocampal neurons accumulate extremely large amounts of Ca. This concentration is much higher than found for mitochondria of physiologically stimulated (Pivovarova et al, 1999(Pivovarova et al, , 2002 or even injured (Taylor et al, 1999) neurons but comparable with the Ca loads known to induce the release of cytochrome c and apoptosis-inducing factor in isolated mitochondria (Petit et al, 1998;Andreyev and Fiskum, 1999;Chalmers and Nicholls, 2003).…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, direct measurements of total Ca in individual mitochondria show that mitochondria of NMDA-overstimulated hippocampal neurons accumulate extremely large amounts of Ca. This concentration is much higher than found for mitochondria of physiologically stimulated (Pivovarova et al, 1999(Pivovarova et al, , 2002 or even injured (Taylor et al, 1999) neurons but comparable with the Ca loads known to induce the release of cytochrome c and apoptosis-inducing factor in isolated mitochondria (Petit et al, 1998;Andreyev and Fiskum, 1999;Chalmers and Nicholls, 2003).…”
Section: Discussionsupporting
confidence: 50%
“…If OGD persists for more than a few minutes after the onset of anoxic depolarization, synaptic transmission will remain compromised, causing irreversible damage to neurons (Balestrino et al 1989;Rader and Lanthorn, 1989). Taylor et al (1999) showed that both synaptic transmission and a rise in intracellular Cl Ϫ (assessed with x-ray electron analysis) failed to recover by 30 min after OGD in the adult hippocampal slice. However, Wang et al (1999) reported that the ionic distribution had returned to pre-hypoxia levels on reoxygenation, although 70% of the neurons remained depolarized and unresponsive to synaptic stimulation.…”
Section: Ogd Effects On Intracellular CL ؊ and Synaptic Transmissionmentioning
confidence: 99%
“…In contrast, if anoxia is prolonged or if adult hippocampal slices are subjected to OGD under conditions that model cerebral ischemia, in vivo, the loss of synaptic transmission may become irreversible (Zhu and Krnjević, 1999). Furthermore, the ionic imbalance in Na ϩ , K ϩ , Ca 2ϩ , and Cl Ϫ worsens during reoxygenation, causing irreversible damage to area CA1 neurons (Taylor et al, 1999;LoPachin et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the release of glutamate in response to a combined effect of an [Na + ] load and oxidative stress was measured in isolated nerve terminals over an incubation for 15 min. Exposure to hydrogen peroxide (100 lM) had no effect on the release of glutamate, but significantly enhanced the Ca (Hansen 1985) and have been shown to be crucial in overall cellular injury (Silver et al 1997;Taylor et al 1999;Zhang and Lipton 1999). Na + entry occurs during oxygen deprivation (Stys et al 1992;Silver et al 1997), but the disruption in [Na + ] i homeostasis is aggravated during reperfusion (Rose et al 1998;Taylor et al 1999).…”
mentioning
confidence: 99%
“…Exposure to hydrogen peroxide (100 lM) had no effect on the release of glutamate, but significantly enhanced the Ca (Hansen 1985) and have been shown to be crucial in overall cellular injury (Silver et al 1997;Taylor et al 1999;Zhang and Lipton 1999). Na + entry occurs during oxygen deprivation (Stys et al 1992;Silver et al 1997), but the disruption in [Na + ] i homeostasis is aggravated during reperfusion (Rose et al 1998;Taylor et al 1999). Reactive oxygen species have been shown to be produced in excess during reperfusion following an ischemic period (Cao et al 1988;Halliwell 1992).…”
mentioning
confidence: 99%